OPTIMIZING HALAL ZONE LAYOUTS IN INDUSTRIAL ESTATES FOR WAREHOUSING AND DISTRIBUTION: A SPATIAL MODELING APPROACH UTILIZING QGIS - Fajar Azhari Julian; Ahmad Nur Ihsan Purwanto; Muhammad Roihan Zainuddin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study develops a comprehensive spatial modeling framework for optimizing halal zones dedicated to warehousing and distribution within industrial estates in Indonesia. Employing Geographic Information System (GIS) tools—particularly QGIS—the research integrates buffering, overlay, and zoning analyses to identify and evaluate potential halal-compliant industrial areas based on accessibility, land suitability, and contamination risk. Data from West Java’s industrial corridors reveal four viable sites (KM42, KM62, KM71B, and KM72A), with KM72A demonstrating superior strategic positioning due to high connectivity, low contamination risk, and ample capacity. The proposed model conceptualizes halal zones as integrated spatial entities designed to ensure strict product segregation, traceability, and adherence to Islamic principles. The study bridges theoretical constructs of halal assurance with pragmatic spatial planning methodologies, offering a replicable GIS-based approach to halal industrial zoning. From a policy perspective, it provides actionable insights for governments and industry actors to strengthen halal logistics infrastructure, thus supporting Indonesia’s ambition to become a global halal hub. The fusion of geospatial analytics and halal governance in this study represents a strategic advancement toward transparent, efficient, and sustainable halal industrial ecosystems.